2021
DOI: 10.1021/acs.est.1c01654
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Ammonium Compounds: Bioaccumulation Potentials in Humans and Levels in Blood before and during the Covid-19 Pandemic

Abstract: Quaternary ammonium compounds (QACs) are commonly used in a variety of consumer, pharmaceutical, and medical products. In this study, bioaccumulation potentials of 18 QACs with alkyl chain lengths of C8–C18 were determined in the in vitro–in vivo extrapolation (IVIVE) model using the results of human hepatic metabolism and serum protein binding experiments. The slowest in vivo clearance rates were estimated for C12-QACs, suggesting that these compounds may preferentially build up in blood. The bioaccumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 64 publications
2
51
0
Order By: Relevance
“…In addition to the debatable toxicity impact on prenatal and maternal animals and humans, a study also showed the potential penetration of QACs into bloodstreams, where QACs were detected in 80% of 43 human volunteers ( Hrubec et al, 2021 ). A similar study showed increasing detection frequency and significantly higher concentration of total QACs (15 QACs) in blood samples collected during the COVID-19 pandemic (median concentration = 6.04 ng/mL) compared to the samples collected before the pandemic (median concentration = 3.41 ng/mL), with an overall increase of 77% ( Zheng et al, 2021 ). Although no biochemical alterations in the body tissues were observed, the low clearance rate of QACs in the liver indicated their high bioaccumulation.…”
Section: Toxicity Of Qacs To Aquatic Organisms and Humanmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition to the debatable toxicity impact on prenatal and maternal animals and humans, a study also showed the potential penetration of QACs into bloodstreams, where QACs were detected in 80% of 43 human volunteers ( Hrubec et al, 2021 ). A similar study showed increasing detection frequency and significantly higher concentration of total QACs (15 QACs) in blood samples collected during the COVID-19 pandemic (median concentration = 6.04 ng/mL) compared to the samples collected before the pandemic (median concentration = 3.41 ng/mL), with an overall increase of 77% ( Zheng et al, 2021 ). Although no biochemical alterations in the body tissues were observed, the low clearance rate of QACs in the liver indicated their high bioaccumulation.…”
Section: Toxicity Of Qacs To Aquatic Organisms and Humanmentioning
confidence: 75%
“…A recent paper by Agathokleous et al (2022) further suggested including hormesis while evaluating the effects and risks of QACs as the linear-no-threshold (LNT), and threshold dose-response models are unable to identify or predict their toxic effects ( Agathokleous et al, 2022 ). The scientific evidence on enhanced metabolic stability, particularly in longer alkyl chain QACs, and the potential bioaccumulation of QACs in humans has dramatically raised additional concerns on the toxicity of QACs ( Zheng et al, 2021 , Seguin et al, 2019 ). Hence, there is a need for a proper evaluation of the safe usage of QACs, including epidemiological study and risk assessment, as well as alternatives to QACs for disinfecting applications.…”
Section: Toxicity Of Qacs To Aquatic Organisms and Humanmentioning
confidence: 99%
“…Quaternary compounds are common in personal care products, pharmaceuticals, and anti-static agents. Their prevalent use in disinfectants, including more than half of EPA-registered products for eliminating SARS-CoV-2, is a likely cause of increased human exposure, demonstrated by the doubling in blood levels of some quaternary ammonium compounds since before the COVID-19 pandemic 39,40 . In our oligodendrocyte-specific cytotoxic hits, quaternary compounds as a class were enriched, and in a 3-D model of human prenatal brain development, our data show that these chemicals are specifically cytotoxic to human oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these mechanistic studies on animals, QAC residue was identified in human blood to a total concentration of QACs at 10–150 nM ( Hrubec et al, 2021 ). The levels of QACs in human blood (6.04 ng/mL) were significantly higher than those before the pandemic outbreak (3.41 ng/mL) due to the effect of COVID-19 ( Zheng et al, 2021 ). Recent studies also reported that QACs were detected in human breast milk ( Zheng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 89%